English as a second language teachers' perceptions of care in an anti-immigrant climate. Issue 4 (1st October 2020) - Dávila, Liv T.; Linares, Rebecca E.
ABSTRACT: This qualitative study applies ethic of care and language ideological orientations to analyze how four middle and high school English as a Second Language (ESL) teachers perceived of care in their relationships with multilingual, multiracial, and multicultural ESL students with diverse immigration backgrounds. Findings show how the focal teachers sought to demonstrate care in their classrooms by engaging in pedagogical reflexivity and by upholding translanguaging stances regardless of their own linguistic backgrounds to encourage and facilitate their students' native language and literacy development. Data analysis revealed that empathy and trust were integrally embedded in teachers' ideologies and approaches. Implications for teaching and teacher education are discussed.